Use of Patient Transfer Aids to Reduce the Risk of Musculoskeletal Disorders in Nurses in the Emergency Department: Literature Reviews - Minarko, Agustinus; Dewi, Yulis Setiya; Suadnyani, Ni Ketut (GLOBAL HEALTH SCIENCE GROUP, 2024)
Introduction: Nurses in emergency installations have a job that has a high risk of developing musculoskeletal disorders due to their workload. An activity that is often carried out by nurses is transferring patients, where this activity has the potential risk of increasing physical burden and musculoskeletal injuries on nurses. The effort to reduce the risk of musculoskeletal disorders in nurses is by using patient transfer aids. The aim of this study is to determine the use of patient transfer aids to reduce the risk of musculoskeletal disorders in nurses in the emergency department. Method: The method used is a literature review with six databases (Scopus, Science Direct, Web of Science, CINAHL, ProQuest, and PubMed) in January 2024. Research design inclusion criteria in this study include cohort studies, case reports, research and development, RCTs, descriptive correlational studies, and experimental studies. Articles published in 2017–2023 in English involving a population of nurses and/or health workers who carry out patient transfers. Data analysis was carried out using the researcher's critical thinking and PRISMA. Results: The use of patient transfer aids will reduce nurses' workload and reduce the risk of musculoskeletal disorders. Various types of patient transfer aids can be used, such as sliding sheets or slides, friction-reduction sheets, glide sheets, ergonomic belts, air-assisted transfer devices, lift velocities, motorized patient transfer devices, and prototype patient transfer aids. Conclusion: Patient transfer aids can significantly reduce the risk of musculoskeletal disorders in nurses in the emergency department.